Reproductive calendar of the Zenú and Embera indigenous peoples of the Eyabida and Chamibida subgroups from Antioquia (Colombia) - Alejandra Milena Valencia González; érika María Valencia Cortés; María Mercedes Arias Valencia; Hugo Alberto Múnera Gaviria (Universidad de Antioquia, 2015)
Objective.This work sought to compare the reproductive calendar of the Zenú and Embera ethnicities of the Eyabida and Chamibida subgroups in Antioquia, Colombia from 2011 to 2013. Methodology. This was a sociodemographic study of purposive sampling through the reproductive history technique, conducted with 165 indigenous women older than 10 years of age. Results. The reproductive calendar is characterized by an age of menarche between 12 and 13 years for both ethnicities; entry to union with a partner occurs 30 months and more in all groups; the first pregnancy 7.9 months after the entry to union with a partner for the Eyabida, 14.0 months for the Chamibida, and 11.3 months for the Zenú; the first delivery happens at 15 years of age among the Zenú, at 16 and 17 for the Eyabida and Chamibida, respectively. The use of Western contraceptive methods is highlighted in the ethnicities. Conclusion. For the ethnicities studied, early ages of onset of reproductive life are noted, along with the fastness of the divergent pattern conserved since the late 1990s for the Chamibida and the growing use of contraceptive methods to limit the number of children.